Gait-cycle characteristics and running economy in elite Eritrean and European runners - Santos-Concejero, J.; Olivan, J.; Mate-Munoz, J. L.; Muniesa, C.; Montil, M.; Tucker, R.; Lucia, A. (International Journal of Sports Physiology and Performance, 2015)
Purpose: This study aimed to determine whether biomechanical characteristics such as ground-contact time, swing time, and stride length and frequency contribute to the exceptional running economy of East African runners. Methods: Seventeen elite long-distance runners (9 Eritrean, 8 European) performed an incremental maximal running test and 3 submaximal running bouts at 17, 19, and 21 km/h. During the tests, gas-exchange parameters were measured to determine maximal oxygen uptake (VO2max) and running economy (RE). In addition, ground-contact time, swing time, stride length, and stride frequency were measured. Results: The European runners had higher VO2max values than the Eritrean runners (77.2 ± 5.2 vs 73.5 ± 6.0 mL · kg-1 · min-1, P = .011, effect sizes [ES] = 0.65), although Eritrean runners were more economical at 19 km/h (191.4 ± 10.4 vs 205.9 ± 13.3 mL · kg-1 · min-1, P = .026, ES = 1.21). There were no differences between groups for ground-contact time, swing time, stride length, or stride frequency at any speed. Swing time was associated with running economy at 21 km/h in the Eritrean runners (r = .71, P = .033), but no other significant association was found between RE and biomechanical variables. Finally, best 10-km performance was significantly correlated with RE (r = -.57; P = .013). Conclusions: Eritrean runners have superior RE compared with elite European runners. This appears to offset their inferior VO2max. However, the current data suggest that their better RE does not have a biomechanical basis. Other factors, not measured in the current study, may contribute to this RE advantage.